2021
DOI: 10.1007/s11121-021-01328-2
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors and Barriers Towards Initiating and Maintaining Strength Training in Women: a Systematic Review and Meta-synthesis

Abstract: Strength training (ST) or resistance training is important in the development and maintenance of musculoskeletal and cardiovascular health in women of all ages; however, uptake of ST amongst women is low. To improve female musculoskeletal health, it is vital that more women are encouraged to participate in ST to maintain musculoskeletal integrity. This systematic review aimed to identify motivators and barriers to women initiating and maintaining ST. Following protocol registration and systematic search, studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…For example, our participants suggested that targeted, specific messages to older adults who consider themselves as active would increase their motivation to engage and meet the guidelines [ 37 ]. Thus, we have added to the growing number of reports suggesting that a lack of detailed guidance on exercise guidelines is a major barrier for older adults [ 23 , 38 , 39 , 40 , 41 ]. The strength component that is embedded within the CMO PAG infographic does not (yet) display important variables such as intensity of effort and session duration as it does for its well-known, and better adhered to aerobic guidelines [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, our participants suggested that targeted, specific messages to older adults who consider themselves as active would increase their motivation to engage and meet the guidelines [ 37 ]. Thus, we have added to the growing number of reports suggesting that a lack of detailed guidance on exercise guidelines is a major barrier for older adults [ 23 , 38 , 39 , 40 , 41 ]. The strength component that is embedded within the CMO PAG infographic does not (yet) display important variables such as intensity of effort and session duration as it does for its well-known, and better adhered to aerobic guidelines [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The strength component that is embedded within the CMO PAG infographic does not (yet) display important variables such as intensity of effort and session duration as it does for its well-known, and better adhered to aerobic guidelines [ 13 ]. Not performing an evidence-based dose of strength training will result in an absence of substantial benefit, another barrier to strength training participation and adherence [ 38 ]. If older adults are not able to benefit from their strength training, they lose their (subjective and objective) ‘fitness,’ and subsequently become less willing and less able to participate in resistance training at intensities or durations that are required to maintain their strength and health [ 5 , 38 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations